Plan de Gestión para el Desarrollo del Proyecto Módulo de Tratamiento de Aguas Residuales del Parque Tecnológico Ambiental de Alajuela - Alpízar-Barrantes, Luis Francisco; Castro-Abarca, María Auxiliadora; González-Alvarado, Fabián (InstitutoTecnológico de Costa Rica, 2013)
The Wastewater Treatment Module of the Environmental Technology Park project is a challenge for the Municipality of Alajuela, as it combines incompatible characteristics such as the project´s technical and bureaucratic complexity, it´s strategic importance for the Institution, versus the Municipality´s shortcomings in project management. Such characteristics leads to expect that there is a high risk for the project to be unsuccessful if the Municipality manages it in the same way they have been working so far. So the main objective of this investigation was to provide a Management Plan for the project, as a tool to help maximize its chances for success. This document consists of two major parts: the formal research work, which includes chapters 1 to 5, and explains according to the formal research methodology, how the Management Plan was developed; and the Management Plan, which contains the auxiliary plans of the nine knowledge areas. The proposed Plan covers the whole of the project´s life cycle, so it focuses predominantly towards the results of its main phases, rather than tasks or specific deliverables. It is expected that this Plan will serve as a general guide for the development of a great length and complexity project.
Proyecto de Graduación (Maestría en Gerencia de Proyectos). Instituto Tecnológico de Costa Rica. Área Académica de Gerencia de Proyectos, 2012.
Keywords: Gestión de proyectos; Agentes contaminantes; Contaminación del agua; Planta de tratamiento; Contaminación hídrica